2x-3(4-x)=5+4(2x+1)

Simple and best practice solution for 2x-3(4-x)=5+4(2x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-3(4-x)=5+4(2x+1) equation:


Simplifying
2x + -3(4 + -1x) = 5 + 4(2x + 1)
2x + (4 * -3 + -1x * -3) = 5 + 4(2x + 1)
2x + (-12 + 3x) = 5 + 4(2x + 1)

Reorder the terms:
-12 + 2x + 3x = 5 + 4(2x + 1)

Combine like terms: 2x + 3x = 5x
-12 + 5x = 5 + 4(2x + 1)

Reorder the terms:
-12 + 5x = 5 + 4(1 + 2x)
-12 + 5x = 5 + (1 * 4 + 2x * 4)
-12 + 5x = 5 + (4 + 8x)

Combine like terms: 5 + 4 = 9
-12 + 5x = 9 + 8x

Solving
-12 + 5x = 9 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
-12 + 5x + -8x = 9 + 8x + -8x

Combine like terms: 5x + -8x = -3x
-12 + -3x = 9 + 8x + -8x

Combine like terms: 8x + -8x = 0
-12 + -3x = 9 + 0
-12 + -3x = 9

Add '12' to each side of the equation.
-12 + 12 + -3x = 9 + 12

Combine like terms: -12 + 12 = 0
0 + -3x = 9 + 12
-3x = 9 + 12

Combine like terms: 9 + 12 = 21
-3x = 21

Divide each side by '-3'.
x = -7

Simplifying
x = -7

See similar equations:

| -7-3x=-2x | | x+3/5=4/7 | | 4c^2d^6-7c^2d^6= | | 0.4(x+2.2)=5.4 | | x^2+5x-5=0 | | 5+2(3Y-1)=7Y+6 | | x+3/5=2/3 | | 2x-3=14x | | 6x^4-7x^3+8x^2-7x+2=0 | | 1.4-3=2+h | | x^4+2x+2=0 | | 0.3(k-0.2)=0.6 | | 5x^2-4x-2=0 | | 12+3x=x | | 8x^3+6x^2-5x+1=0 | | 140-7x=29x+16 | | 2x-9=x | | -3x-1-5x+4= | | t^2=3t+7 | | 9-7x=108-28x | | 9-2x=x | | 6+5x=x | | x-2(x-1)=4-3(x-2) | | 13-8z=7 | | 12+5=11+12x | | -3(x-7)+2= | | 9(2-a)=63 | | 3(2+5m)=-54 | | 17(x-2)=34 | | 17(x-2)= | | 10-2(x+3)=3+3(2x+5) | | 4b-(9b-8)= |

Equations solver categories